(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Saudah, Zumaidar, Darusman, Fitmawati, Roslim DI, Ernilasari. 2022. Ethnobotanical knowledge of Etlingera elatior for medicinal and food uses among ethnic groups in Aceh Province, Indonesia. Biodiversitas 23: 4361-4370. The tribes in Aceh Province have been using Etlingera elatior for various medicinal purposes and as a spice in their culinary. Nonetheless, detailed information on the uses of E. elatior among communities in Aceh is lacking. Therefore, this research aimed to explore the ethnobotanical knowledge among local tribes in Aceh regarding the uses of E. elatior for food and medicine. This research was conducted on eight ethnic groups in Aceh Province (i.e., Acehnese, Gayo, Alas, Aneuk Jamee, Kluet, Tamiang, Singkil, and Simeulue). The data collection was carried out by using semi-structured interviews and field observation. A total of 240 respondents (135 male and 105 female) were selected purposively to obtain local knowledge on the uses, processing techniques and modes of application of E. elatior for medicinal and food purposes. Descriptive statistics were used to analyze the data to determine the level of knowledge and plant parts used, both measured in fidelity level (FL). The results showed that men, elderly people and farmers had more knowledge about the uses of E. elatior as medicine and food ingredients. Traditional medicines made from this herb were used to cure coughs, sprains, postpartum and earaches. Makjun sejuk, pareng, lampok and tapal were the concoction used in traditional medicine. Stem and fruit were the most commonly used plant parts for medicinal herbs, while pounding was the most common processing technique followed by squeezing and grinding either singly or in a mixture used by drinking and rubbing. The uses of E. elatior in food were found in several local dishes with the most common use in a curry called Pliék U. Flower buds and fruit was the most commonly used part in food ingredients. Despite the unique and high uses of E. elatior among tribes in Aceh, the gap in knowledge, especially between the older and younger generations, might impact the loss of local wisdom regarding the plant.